SEROPREVALENCE OF BACILLUS ANTHRACIS PROTECTIVE-ANTIGEN IN NINE DISTRICTS OF CENTRAL PUNJAB, PAKISTAN - H. Rashid; K. Muhammad; M. Rabbani; M. S. Khan1. M. Z. Shabbir; A. Ahmad; M. A. Ali; B. Jayarao2 (Journal of Animal and Plant Sciences, 2020)
Anthrax is a deadly and highly contagious, zoonotic disease caused by Bacillus anthracis. It is an acute, febrile disease of warm-blooded animals and humans. This study was conducted to investigate antibodies against anthrax (Protective-antigen) in four species of domestic animals (cattle, buffalo, sheep and goat) in nine districts of Punjab, Pakistan. The serum samples of the animals (n=680) were processed using indirect ELISA to determine antibodies against Bacillus anthracis protective-antigen (PA). The results showed that 23/120 (19.2%) cattle, 37/101 (36.6%) buffaloes, 124/285 (43.5%) goats and 74/174 (42.5%) sheep have protective level of anti-PA antibodies. Overall, seroprevalence of anti-PA antibodies was 37.9 % in 680 animals. Maximum seroprevalence was recorded in Lahore (82.4%) followed by Gujranwala (80.4%), Sahiwal (72.7%), Chakwal (63.6%), Sargodha (54.3%), Faisalabad (15.2%), Sheikhupura (14.1%), DG Khan (5.5%) and Attock (0%), respectively. It was concluded that eight out of nine districts of Punjab had animals positive for antibodies against PA of B. anthracis and all of the four species of domestic animals were seropositive. Continuous monitoring of animals for B. anthracis is highly recommended for keeping the threat under control.
Keywords: Bacillus anthracis; domestic animals; indirect ELISA; Punjab